LAS COMPLEJIDADES DE LA SEGURIDAD Y LA SOBERANÍA ALIMENTARIA EN VENEZUELA - Francisco Domínguez (Revista de Políticas Públicas, 2016)
Security and food sovereignty are usually closely linked, even more so in Venezuela, but due to the structural economic characteristics of its oil economy, and, since 1999, due to the transformations in which this nation embarked from the onset of the Bolivarian Revolution initiated by Hugo Chavez Frias. Social justice, especially poverty eradication, and all the consequences associated with this scourge so common in Latin America, such as labor informality, socio-political exclusion of large sections of the poor and destitute, and, above all, child mortality, malnutrition and undernourishment, have been priority objectives of the Bolivarian process. Because of that, food security has been proclaimed as a constitutional right, specifically Art.305 of the Constitution of the Bolivarian Republic of Venezuela enshrines the right to food as a fundamental state policy. The achievements in food security are noteworthy, leading Bolivarian Venezuela to merit two FAO official recognitions. However, the achievements in food sovereignty are more modest, the main obstacle being the century-old highly specialized structure around oil of this South American nation’s economy. A second obstacle, more contemporary but no less serious in achieving not only sovereignty but especially food security is the economic war that, as in the Chile of Salvador Allende, seeks to erode the base of political support for bolivarianism through hoarding, smuggling food staples and fuel, large-scale currency speculation, and the use of fracking to induce oil prices to collapse levels as a political weapon against governments and regimes that Washington detest. And, as in Chile, such destabilisation plans can be lethal.